Hubungan Pengetahuan Sikap dan Budaya Dalam Pemberian Imunisasi Hepatitis B Pada Bayi 0-7 Hari di Puskesmas Gumpang Kec.Putri Betung Kab.Gayo Lues Tahun 2023 - Elmika Murdalena; Mediana Sembiring; Rabiah Saidatul (Jurnal Medika Nusantara, 2024)
Background: The first Hepatitis virus was discovered by Baruch Blum Berg in 1965 and until now Hepatitis A, B and C are still serious world health problems because they have the potential to cause morbidity and mortality. Apart from that, it is also known that the cause of non-B and non-C chronic hepatitis is a fatty liver. Around two billion people in the world have been infected with the Hepatitis B virus and 360 million of them have chronic infection which has the potential to develop into cirrhosis and hepatocellular carcinoma with a death rate of 250,000 per year. Objective: To determine the relationship between knowledge, attitude and culture in providing Hepatitis B immunization to babies 0-7 days old at the Gumpang Community Health Center, Putri Betung District, Gayo Lues Regency in 2023. Method: In this research the author used a descriptive method or a research method carried out using The main goal is to describe a situation objectively. Results: Based on the results of research conducted at the Gumpang Community Health Center, Putri Betung District, Gayo Lues Regency with 69 mothers who were respondents, it shows that the majority of respondents' attitudes were positive about hepatitis B immunization 0-7 days was good, amounting to 58 people (84%) of the total respondents.